Climate Change and Resilience of Independent Villages (IDM), Ecological Resilience Index (Ikl) Review and Nature-Base Solutions - Retnowati, Arry; Hisbaron, Dyah Rahmawati; Fajarwati, Alia; Isnaini S, Muh; Fajar, Khusnul Intan; Obed, Gonxha (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Village Development Index (IDM) classifies the level of village development into distinct categories, such as Independent Village, Advanced Village, Developing Village, Underdeveloped Village, and Very Underdeveloped Village. Each village is guided to improve its social, economic, and ecological quality. A sound ecological quality also supports resilience and sustainability in its socio-economic conditions. Pendoworejo Village in Girimulyo Subdistrict and Pagerharjo Village in Samigaluh Subdistrict were classified as underdeveloped villages in 2016. However, by 2023, according to the Village Development Index (IDM), both villages had achieved the status of independent villages. the development of the tourism sector has become a key driver for diversifying rural community members' incomes, thereby boosting regional economic development. Sustainable management of the natural environment, based on its ecosystem, is an integral component of Nature-Based Solutions.